Checklist of ground beetles (Coleoptera, Carabidae) deposited in National Insect Museum of Pakistan. (2nd October 2017) - Azadbakhsh, Saeed; Rafi, Muhammad Ather
Abstract: This paper presents the result of investigation of the ground beetles specimens that are stored in the National Insect Museum of Pakistan. A total of 38 species were identified, 12 species – Chlaenius ( Chlaeniostenus ) pulcher Nietner, 1857, Chlaenius ( Chlaeniellus ) koenigi Semenov, 1888, Chlaenius ( Amblygenius ) pretiosus Chaudoir, 1856, Chlaenius ( Chlaenius ) lafertei Guerin-Meneville, 1843, Chlaenius ( Rhysotrachelus ) nepalensis Hope, 183, Chlaenius ( Chlaeniellus ) cookei Andrewes, 1933, Loxoncus ( Loxoncus ) procerus (Schaum, 1858), Heteracantha depressa Brulle, 1834, Anomostomus orientalis Andrewes, 1923, Sericoda lissoptera (Chaudoir, 1854), Galerita ( Galerita ) orientalis Schmidt-Goebel, 1846, Anthia ( Termophilum ) duodecimguttata Bonelli, 1813 – are reported from Pakistan for the first time; in addition, the occurrence of several species in Pakistan was confirmed.